PROGRAM IN EFFORTS TO REDUCE THE PREVALENCE OF LEPROSY IN KAMPUNG BESAR VILLAGE, TELUKNAGA DISTRICT - Elizabeth, Jessica; Firmansyah, Yohanes; Meliyana, Meliyana; Singgih, Rendy (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2024)
The health profile in 2011-2013 released 14 provinces in Indonesia as a region with a high leprosy burden and 19 other provinces with a low leprosy burden. Banten Province in 2011 found 500 new cases with an NCDR of 4.58% and an increase in 2012 and 2013 with an NCDR of 6.75% and 6.09%. Objectives: Reduce the prevalence of leprosy in the work area of the Teluknaga Health Center, Tangerang Regency. Methods: The study used two approaches, namely the data approach and the Blum paradigm approach. Problem identification is made through an epidemiological approach by observing and analysing data from the previous period. Results: The existing problems are the factors of knowledge, attitudes, and behaviour of the community in dealing with leprosy, which is still poor and supported by a dense, arid, and poor ventilation environment. There are still people who have the attitude in the form of stigma that leprosy is a curse and do not agree that people affected by leprosy participate in joint activities. The behaviour of most people is still not good because they have never attended counselling about leprosy and have never conducted a leprosy detection check. In implementing the activities Plan, Do. Check and Action (PDCA). Conclusions: The existing problems are the factors of knowledge, attitudes, and behaviour of the community in dealing with leprosy, which is still poor and supported by a dense, arid, and poor ventilation environment.